Best Friends - Chancellor, Deborah; Illustrated by Secheret, Jessica (London QED, 2011)
Displays a fresh, modern approach to girls' passions and interests. From arts and crafts to keeping fit and handling friendships, this book includes the activities that shape a young girl's life.
Includes Color Illustrations
Keywords: Friends Forever -- Forgive And Forget -- Best Friends Quiz